Cote d'Ivoire : Poverty Reduction Strategy Paper: Progress Report. (IMF Staff Country Reports; Country Report ;, 2012)
This paper presents the Poverty Reduction Strategy Implementation Progress Report for Cote d'Ivoire. Since the end of the crisis in April 2011, Cote d'Ivoire has gradually recovered economic activity and social cohesion, as reflected in the reopening of banks, schools and health centers, markets, and industrial enterprises. Financing of the poverty reduction strategy is provided largely through budget resources and assistance from the government's technical and financial partners (TFP). Assistance from the TFP may also take the form of project grants or program grants.